2009 Fourth International Conference on Communications and Networking in China 2009
DOI: 10.1109/chinacom.2009.5339964
|View full text |Cite
|
Sign up to set email alerts
|

Management and service-aware networking architectures (MANA) for future Internet — Position paper: System functions, capabilities and requirements

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 2 publications
0
20
0
2
Order By: Relevance
“…A one-to-one mapping between CANMgrs and IntraNRMs has been adopted. The distributed management and control plane [9] enables large-scale provisioning capabilities and supports the integration of independent NPs in multi-domain scenarios. Either the IntraNRM can be evolved to include CAN management functionalities, or a separate entity can be deployed.…”
Section: Hybrid Multicast Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A one-to-one mapping between CANMgrs and IntraNRMs has been adopted. The distributed management and control plane [9] enables large-scale provisioning capabilities and supports the integration of independent NPs in multi-domain scenarios. Either the IntraNRM can be evolved to include CAN management functionalities, or a separate entity can be deployed.…”
Section: Hybrid Multicast Overviewmentioning
confidence: 99%
“…While full network virtualization is challenging in terms of seamless deployment, more "light" solutions can be attractive by being deployed as parallel data planes [8], logically separated but under the coordination of a single management and control plane. In [9], several research challenges related to the management and control planes are identified. The proposed solution addresses some of them.…”
Section: Introductionmentioning
confidence: 99%
“…Future Internet will have many of its functions based on programmability of network resources [18]. Handling programmability [20][21] in virtual environments is an essential requirement in realizing Future Internet.…”
Section: Other Supporting Systemsmentioning
confidence: 99%
“…Future Internet must tackle the lack of built-in facilities to support non-basic functionalities in order to offer service-aware functionality [1]. Traditionally, the growth of the Internet and convergent services in the IP layer has been solved, as far as performance concerns, by increasing bandwidth and computational power in the edge devices.…”
Section: Introductionmentioning
confidence: 99%